Crocetin: A Systematic Review - Guo, Zi-Liang; Li, Mao-Xing; Li, Xiao-Lin; Wang, Peng; Wang, Wei-Gang; Du, Wei-Ze; Yang, Zhi-Qiang; Chen, Sheng-Fu; Wu, Di; Tian, Xiu-Yu (Frontiers in Pharmacology, 2022)
Crocetin is an aglycone of crocin naturally occurring in saffron, which is produced in biological system by hydrolysis of crocin as a bioactive metabolite. It exists in many medicinal plants, the desiccative ripe fruit of the cape jasmine belonging to Rubiaceae family and stigmas of the saffron plant of the Iridaceae family. Modern pharmacology indicates that crocetin possesses cardioprotective, hepatoprotective, neuroprotective, anti-depressant, anti-viral, anti-cancer, atherosclerotic, anti-diabetics, memory enhancer properties. Even though the poor bioavailability of crocetin makes it difficult to achieve their therapeutic applications, derivatization and formulations preparation technologies have broadened the application prospect for crocetin. In order to promote the research and development of crocetin, we will summarize the distribution, preparation and production, total synthesis and derivatization technology, pharmacological activity, pharmacokinetics, drug safety, drug formulations and preparation research of crocetin.